Ausencia de la figura paterna y su incidencia en la salud mental de una adolescente de 13 años del Colegio Nacional Diez de Agosto - Vera Fernández, Leonela Alexandra (2023)
This case study establishes the incidence of the absence of the father figure in the mental health of a 13-year-old girl from the national school "Diez de Agosto". of canton Montalvo, which was possible to establish through tools such as interviews, clinical observation, clinical history and application of psychometric tests. For this, opportune areas were considered to achieve a broad expectation about the context to be investigated, these being the paternal absence, mental health, adolescents and depression. It was possible to understand how the absence of the father figure, however different the causes, manages to affect the mental health of an adolescent, so that this is affected negatively, highlighting the development of major depressive disorder, among the different conditions that can occur due to this situation. The main results show that in the cognitive, affective, socio- school and somatic behavior it is important to take into account the absence of the father figure as the source of the different difficulties presented by adolescents. The proposal, presented according to the results, addresses a set of cognitive behavioral therapy techniques to improve the situation of the patient.